Two jatropha karyotypes constructed from meiotic pachytene chromosomes: Pericentric distribution of heterochromatin and variation in repetitive DNAs - Muakrong, Narathid (PLoS One, 2018)
Jatropha (Jatropha curcas) is an oil-bearing plant used for biodiesel production. Construction of its standard karyotype and identification of the euchromatin/heterochromatin distribution associated with gene expression and meiotic recombination are essential to fully characterize its genome. Here, we developed a J. curcas karyotype based on meiotic pachytene chromosomes. In addition, a karyotype of J. integerrima, a useful species for jatropha breeding, was also constructed. Five out of eleven J. curcas chromosomes were metacentric, but only two were metacentric in J. integerrima. Almost all of the heterochromatin was distributed around the pericentric regions. The interstitial and distal regions were euchromatic without heterochromatic knobs, except for small heterochromatin regions associated with the subtelomeric repeat sequence JcSat1. These pericentric heterochromatin distribution patterns, together with chromosome structure data and the results of FISH probing with rDNA and JcSat1, allowed us to classify all chromosomes of both species. The two species had two 35S rDNA loci and one 5S rDNA locus; one 35S rDNA locus in J. integerrima was located on the interstitial region of the short arms. In addition, JcSat1 was found at only the heterochromatic ends of the J. curcas chromosome, not the J. integerrima chromosome. Despite the same chromosome number, the two pachytene chromosome-based karyotypes suggest variation in chromosome structure and distribution of repetitive DNAs in these two species.